GREEN TEA EXTRACT EFFECT ON BLOOD GLUCOSE LEVEL AND LIVER HISTOPATHOLOGY IN DIABETIC MICE - Diana Holidah; Fransiska Maria Christianty; Wilda Zidni Ilma (UNEJ e-Proceeding)
Diabetes mellitus is a disorder of hyperglycemia andglucose intolerance due to insulin deficiency,impaired of insulin receptor or both (Unwin et al.,2009). There are generally two types of diabetes aretype 1 diabetes (pancreatic beta cell damage causedabsolute insulin deficiency) and type 2 (acombination of a lack of insulin production andsecretion and sensitivity to insulin receptor) (Dipiroet al, 2008).Diabetes mellitus disease is increasing rapidly inworlwide. The incidences in 2010 were about 285million people and It has been estimated that by theyear 2025, the global incidence of diabetes wouldincrease to 350 million (International diabetesfederation, 2006).In diabetes, activation of hepatic gluconeogenesisenzymes can increase glucose production and thuscontribute to increase blood glucose which coulddeteriorate diabetes (Sundaram et al., 2013). Thestate of diabetes characterized by decreased insulinsensitivity is the major cause of NAFLD (Non -Alcoholic Fatty Liver Disease), because in diabetesstate occurs disorders of glucose metabolism and fatso that could result in fibrosis, infiltration,necroinflamation, to acute liver disease (Marchesiniet al., 2001).Treatment of diabetes mellitus is chronic and longlife, causing undesirable side effects (Unwin et al.,2009). Metformin is an oral hypoglycemic agent,which belongs to the class known as the biguanides.Metformin is now widely used as one of themainstays in the management of type 2 diabetes.Metformin reduces fasting plasma glucoseconcentration by reducing rate of hepatic glucoseproduction via gluconeogenesis and glycogenolysis.Metformin improves glycemic control asmonotherapy and in combination with other oralantidiabetic agents, such as sulfonylureas andthiazolidinediones (Frendell et al. 2003).Several plant extracts are known to have antidiabeticproperties and a large number of compounds fromplant extracts have been reported to have beneficialeffects for treatment of diabetes mellitus (Anhauser,2003). Tea (Camellia sinensis L.) is one of plant thatcan decrease blood glucose. Green tea is producedby enzymatic inactivation of the leaves of Camelliasinensis followed by rolling or comminution anddrying. In the manufacturer of green tea, theenzymatic inactivation achieved by steam or panfiring treatment to preserve natural polyphenolswith respect to the health promoting properties.Green tea derived products are mainly extracts ofgreen tea in liquid or powder form varying in theproportion of polyphenols (45-90%) and caffeinecontent (0.4-10%). The polyphenolic fraction ofgreen tea, has been reported to have multiplepharmacological actions (Sano et al., 1995).Green tea is an excellent source of polyphenolantioxidants, known as green tea catechins. Theimportant catechins of green tea are epicatechin(EC), epicatechin-3-gallate (ECG), epigallocatechin(EGC) and epigallocatechin-3-gallate (EGCG). Thepolyphenolic fractions of green tea have beenreported to have multiple pharmacological actions.They exhibit potent antioxidant activity in vitro andin vivo. Epidemiologic observation and laboratorystudies have indicated that polyphenolic compoundspresent in the tea may reduce the risk of a variety ofillnesses, including cancer and coronary heartdisease (McKay and Blumberg 2002).Some studies suggest that green tea extract loweredcholesterol levels and blood glucose on mice and rat(Yang et al., 2001). Green tea extract at dose of300mg /kg /day can lower blood glucose in diabeticrats and was also able to reduce the lipids in heartdefects (Babu et al., 2006). Blood glucose loweringactivity of green tea was greater and totalpolyphenol content was higher when compared withblack tea and oolong tea (Holidah et al., 2015).